Musical Composition in the Twentieth Century - Whittall, Arnold -1935 (Oxford Oxford university press, 1999)
This new book builds on Whittall's Music since the First World War. It updates and reshapes the original text and places it in the wider context of twentieth-century serious music before 1918 and after 1975, surveying the immense variety of technical developments in twentieth-century music. Sections of detailed analysis, with particular emphasis on such major figures as Stravinsky, Bartï¿½k, Messiaen, Tippett, and Ligeti, are framed by more concise sketches of a range of twentieth-century composers from Faurï¿½ to Wolfgang Rihm. Extensive musical examples are employed throughout.